Strategies and structures : the processing of relative clauses - Prideaux, Gary Dean (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 1986)
In this monograph, the nature of processing strategies is explored in some detail, with an attempt to cut through the maze of often contradictory and confused proposals concerning the nature and form of various strategies. Once a preliminary conception of the nature of cognitive strategies and a hypothesis of how they interact with linguistic structures has been reached, it will be explored how such strategies are employed by examining experiments which address the role played by certain of these strategies in the comprehension and production of sentences. The authors draw a distinction betwee.